2023
DOI: 10.1186/s13018-023-04379-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of Bowen therapy and tennis ball technique on pain and functional disability in patients with thoracic myofascial pain syndrome

Fareeha Amjad,
Afsheen Khalid

Abstract: Background Thoracic myofascial pain syndrome is a clinical problem arising from the muscles and soft tissues of thoracic region, which include the mid and upper back area. Risk factors associated with myofascial pain syndrome are muscle overuse and repetitive strain, poor posture, trauma or injury, emotional and psychological stresses. The management of myofascial pain syndrome (MPS) typically involves a multidimensional approach that focuses on relieving pain, reducing muscle tension, and impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Rodríguez-Huguet M et al [8] appeared that after applying MFR for 2 weeks, pain in the suboccipital and trapezius muscles improved by about 60%, and the effect was maintained even at 1-month follow-up, and Cabrera-Martos I et al [25] applied it to about 20 people for 4 weeks, and the pain in the suboccipital and levator scapulae muscles improved by about 30%. Amjad F and Khalid A [26] applied release techniques using tennis balls three times a week for 4 weeks to 30 patients with thoracic myofascial pain syndrome, and the pain improved by about 60%. The pain results showed similar results to previous studies, and it is believed that applying MFR using MFR and Duoball to patients with chronic neck pain positively improves pain in the short and long term.…”
Section: Discussionmentioning
confidence: 99%
“…Rodríguez-Huguet M et al [8] appeared that after applying MFR for 2 weeks, pain in the suboccipital and trapezius muscles improved by about 60%, and the effect was maintained even at 1-month follow-up, and Cabrera-Martos I et al [25] applied it to about 20 people for 4 weeks, and the pain in the suboccipital and levator scapulae muscles improved by about 30%. Amjad F and Khalid A [26] applied release techniques using tennis balls three times a week for 4 weeks to 30 patients with thoracic myofascial pain syndrome, and the pain improved by about 60%. The pain results showed similar results to previous studies, and it is believed that applying MFR using MFR and Duoball to patients with chronic neck pain positively improves pain in the short and long term.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise therapy and manual therapy are two physiotherapy interventions that are commonly used in the treatment of calcifying tendinitis of the shoulder, not alone, but in combination with ultrasound or other non-invasive techniques (16).In our study, two manual therapies were applied in addition to ultrasound, widely used in practice, but whose application has been poorly researched and thus confirmed in science. Recently published papers report the effectiveness of Bowen therapy in reducing pain and increasing mobility in myofascial syndromes and chronic pain(22)(23)(24). A pilot study published in 2001 also reported the beneficial effect of Bowen therapy in reducing pain, and increasing functionality and activities of daily living in individuals with frozen shoulders(25).…”
mentioning
confidence: 99%